Relations between Russia and China at the End of the 19th Century - Sobirjonovna, Shomansurova Zilola (Journal of Learning on History and Social Sciences, 2024)
The article examines about the weakening of the central government in China at the end of the 19th century, the aggravation of the country’s socio-political situation, and the strengthening of the western countries’ struggle to take over it.